PENERAPAN REDIS DALAM SISTEM E-OFFICE DESA SUTERA - Riyadi Iskandar; Kartono Kartono; Gandhy Gandhy (LPPM Universitas Widya Dharma Pontianak, 2022)
Administration is something important in government system because if there is no administration then there will be a lot of thing happen like tracking and message will be uncoordinated and those data became hard to find. One important aspect in administration system is speed and that is the reason why author perform testing on administration system in sutera village named nusANTARA and implementing redis strategy in nusANTARA system so the system can be more efficient in handling user. The author uses experimental research designs to make research, while the data collection method used is the study of literature containing scientific books, theses, scientific papers, scientific journals, and other sources that related to the research topic. The system analysis technique used is object-oriented technique with Unified Modelling Language (UML) modeling. The design application uses the Laravel framework and MySQL database management system. This research produce a system that already implemented with redis strategy and compare result between old system and new system. The conclusion of this research is nusANTARA system canoot handle user more than 500 user when test take place which can be solve with implementing redis strategy that can reduce a down server time of nusANTARA. Keywords: Laravel, Redis, Jmeter